2011
DOI: 10.1002/rra.1376
|View full text |Cite
|
Sign up to set email alerts
|

Downstream effects of diversion dams on sediment and hydraulic conditions of Rocky Mountain streams

Abstract: Reduced streamflow via flow diversion has the potential to limit the sediment-transport capacity of downstream channels and lead to accumulation of fine sediments and habitat degradation. To investigate, we examined the effects of variable levels of flow diversion on fine-sediment deposition, hydraulic conditions and geomorphic alteration. Our study consisted of a detailed field analysis pairing reaches above and below diversion dams on 13 mountain streams in north-central Colorado and southern Wyoming USA. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 48 publications
0
51
0
1
Order By: Relevance
“…Comparisons between bypassed and upstream reaches of lowhead RoR dams found higher levels of fine sediment and significantly slower water velocity in 13 bypassed reaches as well as significant differences between upstream and bypassed reaches in 32 of 41 hydraulic variables (Baker et al 2011). Based on their modelling results, Baker et al (2011) also concluded that small, low-gradient streams with smaller-sized substrate were more susceptible to fine-sediment accumulation than large streams. However, RoR dams that are regularly overtopped at high flows are expected to experience fewer discontinuities in the morphological and sediment size distribution of stream channels (Kondolf 1997;Csiki and Rhoads 2013;Kibler and Tullos 2013).…”
Section: Pathway 2: the Presence Of Low-head Damsmentioning
confidence: 95%
See 4 more Smart Citations
“…Comparisons between bypassed and upstream reaches of lowhead RoR dams found higher levels of fine sediment and significantly slower water velocity in 13 bypassed reaches as well as significant differences between upstream and bypassed reaches in 32 of 41 hydraulic variables (Baker et al 2011). Based on their modelling results, Baker et al (2011) also concluded that small, low-gradient streams with smaller-sized substrate were more susceptible to fine-sediment accumulation than large streams. However, RoR dams that are regularly overtopped at high flows are expected to experience fewer discontinuities in the morphological and sediment size distribution of stream channels (Kondolf 1997;Csiki and Rhoads 2013;Kibler and Tullos 2013).…”
Section: Pathway 2: the Presence Of Low-head Damsmentioning
confidence: 95%
“…Although evidence in the peer-reviewed literature specific to RoR hydropower is more limited (n = 31), it suggests that water quality, habitat quantity, and geomorphology can also be affected by RoR hydropower operations (Kubečka et al 1997;Baker et al 2011;Nislow and Armstrong 2012;Bilotta et al 2016). Changes to NFR following diversion of flow can affect water quality mainly through changes to temperature regimes, pH, and dissolved oxygen (Valero 2012).…”
Section: Characteristics Of Flow Diversion For Ror Hydropower and Intmentioning
confidence: 99%
See 3 more Smart Citations